Evaluation of Food Safety and Quality Parameters for Shelf Life Extension of Pulsed Light Treated Strawberries. Issue 6 (6th May 2019) - Cao, Xinang; Huang, Runze; Chen, Haiqiang
Abstract : Abstract: Strawberry is a healthy fruit with numerous health‐benefit compounds. Unfortunately, it is highly perishable and occasionally can be contaminated with foodborne pathogens. The overall goal of this study is to evaluate pulsed light (PL) processing for disinfection of strawberries, extension of shelf life, and preservation of quality attributes and compounds that are beneficial to health. Preliminary screening of PL conditions based on visual appearance of strawberries was conducted, and 3 PL treatments were identified for full evaluation. Salmonella inoculum was artificially deposited onto the skin of strawberries via spot‐inoculation or dip‐inoculation. The 3 PL treatments slightly reduced the level of inoculated Salmonella on strawberries, ranging from approximately 0.4 to 0.8 log reduction. They also slowed down the visible mold development on strawberries by 2 to 4 days compared with the untreated control. Regarding the natural yeasts and molds, the quality attributes (weight loss and firmness), and the bioactive compounds (total anthocyanin, total phenolics, and total antioxidant activity). The 3 PL treatment showed no significant or negligible difference comparing to the control group. Overall, the 3 PL treatments demonstrated potential in extending the shelf life of strawberries. The quality attributes or the bioactive compounds of strawberries showed no significant or minimal change after these PL treatments. Practical Application: Pulsed light (PL) processing for strawberry decontamination and shelf life extension was evaluated. Results demonstrated that PL processing could have the potency to improve strawberry shelf life without significantly affecting the quality and bioactive compounds of strawberries.